1987
DOI: 10.1038/clpt.1987.126
|View full text |Cite
|
Sign up to set email alerts
|

A urinary metabolite ratio that reflects systemic caffeine clearance

Abstract: Systemic caffeine clearance and urinary metabolite profiles were determined in 15 subjects with diverse exposure histories to cytochrome P-450 inducers (cigarette smoke) and inhibitors (oral contraceptive steroids). A correlation was observed between caffeine clearance and a urinary ratio based on the molar recovery of paraxanthine 7-demethylation products relative to a paraxanthine 8-hydroxylation product (r = 0.91; P less than 0.001). Analysis of urinary metabolites was undertaken in a larger population to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
104
1
10

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(128 citation statements)
references
References 0 publications
13
104
1
10
Order By: Relevance
“…In order to select a urinary ratio that accurately reflects caffeine 3-demethylation (and aromatic amine N-oxidation), a pharmacokinetic study was carried out in 12 individuals in whom the levels of caffeine and 15 of its metabolites in blood and urine were measured over a 48-hr period after caffeine dosing (3 mg/ kg). The results indicated that the urinary ratio of [1,7- (37,38).…”
Section: Cytochromes P450mentioning
confidence: 83%
“…In order to select a urinary ratio that accurately reflects caffeine 3-demethylation (and aromatic amine N-oxidation), a pharmacokinetic study was carried out in 12 individuals in whom the levels of caffeine and 15 of its metabolites in blood and urine were measured over a 48-hr period after caffeine dosing (3 mg/ kg). The results indicated that the urinary ratio of [1,7- (37,38).…”
Section: Cytochromes P450mentioning
confidence: 83%
“…2B). These results demonstrate the inducing effect of tobacco smoke on P450IA1 in the lung and on P450IA2 probably in the liver of smokers (4,12). Further molecular analyses are required to determine whether CYP1A2 and other CYPs are expressed in the lungs of smokers.…”
Section: Methodsmentioning
confidence: 98%
“…Apiaceous vegetables (dill weed, celery, parsley, parsnip, carrot) have an inhibitory affect while allium vegetables (garlic, onions, scallions, leeks, and chives) have no effect on P450 1A2 activity when compared with a control diet lacking vegetables [18]. Oral contraceptives and estrogen hormone replacement therapy have also been identified as inhibitors of the metabolic activity of P450 1A2 [11,15,19]. Individuals who are exposed to enzyme inducers or inhibitors in the workplace, such as anesthesiologists exposed to anesthetic chemicals in the operating room, gasoline station attendants exposed to high levels of petroleum, and greenhouse workers exposed to pesticides, may also exhibit altered P450 1A2 metabolic activity [20][21][22][23].…”
mentioning
confidence: 99%
“…Individuals who are exposed to enzyme inducers or inhibitors in the workplace, such as anesthesiologists exposed to anesthetic chemicals in the operating room, gasoline station attendants exposed to high levels of petroleum, and greenhouse workers exposed to pesticides, may also exhibit altered P450 1A2 metabolic activity [20][21][22][23]. Beyond these environmental factors, age and gender have also been shown to affect P450 1A2 metabolic activity with children having higher activity than adults, and men having higher activity than women, though this latter observation is disputed [11,14,15,18,19].…”
mentioning
confidence: 99%
See 1 more Smart Citation